The Use of Fillers by the Students of English Study Program in English Speaking Practice - Yulpia, Tika (Pusat Kajian Bahasa Daerah & Budaya, 2025)
This study examines the use of fillers in speech among students in the Intermediate English-Speaking class at Palangka Raya University during the 2023/2024 academic year. Fillers, which include words, phrases, and clauses that do not carry meaning but serve to fill pauses, play a role in communication by organizing thoughts and managing speech flow. The research aims to classify the types of fillers used and determine which type is most dominant. Using a qualitative descriptive method with content analysis, data were collected through documentation and analyzed based on Rose’s (1998) theory. From 32 recorded speech samples, a total of 306 fillers were identified. The findings revealed that Unlexicalized Fillers (such as